Control tributario en la gestión contable de la empresa Transporte, Minería y Construcción de la ciudad de Huaraz - León Aparicio, Nataly Morayma (2025)
ABSTRACT In the following research, the general objective is to analyze tax control in the accounting management of the company Transporte, Minería y Construction Oncoy Ingenieros S.A.C., Huaraz, 2024. The methodology is basic, a qualitative approach and case research design . An interview with the participants and normative analysis are applied as techniques, and as instruments an interview guide and a document analysis sheet. The results highlight the importance of tax control as a key element for efficient accounting management. Implementing effective tax control is essential to strengthen accounting management, guarantee timely compliance with tax obligations and highlight its impact on strategic decision making, optimization of resources and reduction of legal risks. The case company faced recurring difficulties in complying with its tax obligations, which resulted in fines for lack of knowledge of the regulations and inadequate responses to SUNAT, with the main challenges identified as regulatory complexity, lack of resources and the need to adapt. to constant changes. Therefore, the conclusion highlighted the importance of training, the use of technology and collaboration with external experts as key elements to optimize processes. Keywords: Training, tax control, tax compliance, accounting management. CÓDIGO JEL M41 M42 M49